Effect of infliximab on quality of life in patients with ankylosing spondylitis according to sf-36 questionnaire data - Tatyana Alekseevna Raskina; O A Pirogova; Zh A Pivovarova (Современная ревматология)
Objective: to evaluate the effect of infliximab (INF) on quality of life (QL) in patients with ankylosing spondylitis (AS), by analyzing the results of a SF-36 questionnaire survey. Subjects and methods. Sixty-six male patients, diagnosed with AS (according to the 1984 modified New-York criteria) in its extensive or end stage with a high activity (BASDAI ≥4.0), were followed up. All the patients were divided into 2 groups according to the option of disease-modifying antirheumatic drug therapy: 1) 16 patients who received combination therapy with INF given as a standard regimen at 0, 2, and 6 weeks followed by a regimen of 5 mg/kg body weight and nonsteroidal anti-inflammatory drugs (NSAIDs) in standard doses every 8 weeks; 2) 50 patients who had monotherapy with NSAIDs in the same doses. QL was assessed using the Short-Form 36 (SF-36) questionnaire in patients with AS. Results. The scales evaluating physical health showed the greatest group differences in pain intensity (38.42%; p<0.0001) and the least in the general health status (24.48%; p<0.001). Those assessing mental health displayed statistically significant group differences in vital activity (24.78%; p<0.01).Conclusion. The patients receiving monotherapy with NSAIDs were found to have lower scores in all SF-36 scales than those on combination therapy with INF and NSAIDs.